The implementation of Discovery-Based Multiple Representations Learning (DMRL) to enhance student’s critical thinking skills - Chusni, Muhammad Minan (Kasetsart Journal of Social Sciences, 2023)
The objective of this study is to analyse the effectiveness of DMRL model’s in enhancing students’ critical thinking skills (CTS) on environmental change topics. Futhermore, we use a one-group pretest-posttest research design to examine this effect. There were sixty students in 7th-grade selected using the randomised sampling technique at MTs 2 Sleman as the sample. The instrumen consist of 14 questions of the essay test to obtain the student ability Students score then analysed using Analysis of Variance (ANOVA). This study showed that implementing the DMRL model on environmental change material had significant effects on enhancing students’ CTS. An enhancement in students’ CTS is indicated by an average normalised gain score of 0.35 or in the middle category. Students have the most significant increases in aspect reasoning and analysing while in gender comparison, the female students have more significant improvement than male students with gain of .38 > .28. For further research, the aspect needed to be improved is the clarity assumption. The student still has difficulties even after treatment with gain categories low. However, the DMRL could be optimazed students’ CTS on environmental change material as an alternative learning model.